A Multicenter Open-Label Randomized Controlled Trial of Pancreatic Enzyme Replacement Therapy in Unresectable Pancreatic Cancer. Issue 7 (August 2018) - Saito, Tomotaka; Nakai, Yousuke; Isayama, Hiroyuki; Hirano, Kenji; Ishigaki, Kazunaga; Hakuta, Ryunosuke; Takeda, Tsuyoshi; Saito, Kei; Umefune, Gyotane; Akiyama, Dai; Watanabe, Takeo; Takagi, Kaoru; et al.
Abstract : Objective: Exocrine pancreatic insufficiency may impair the nutritional status in pancreatic cancer (PC), but the role of pancreatic enzyme replacement therapy (PERT) is not fully evaluated. Therefore, we conducted this multicenter open-label randomized controlled trial to evaluate the role of PERT in PC patients. Methods: Patients with unresectable PC receiving chemotherapy were randomly assigned to pancrelipase and nonpancrelipase groups. Patients in the pancrelipase group took oral pancrelipase of 48, 000 lipase units per meal. N -benzoyl-tryrosyl para-aminobenzoic acid (NBT-PABA) test was performed at baseline. Our primary endpoint was change in body mass index (BMI) at 8 weeks. Secondary endpoints were change in other nutritional status at 8 weeks and overall survival. Results: A total of 88 patients were enrolled between May 2014 and May 2016. The NBT-PABA test was lower than the normal range in 90%. There were no significant differences in change in BMI at 8 weeks: 0.975 and 0.980 in the pancrelipase and the nonpancrelipase groups, respectively ( P = 0.780). The other nutritional markers were also comparable. The median overall survival was 19.0 and 12.0 months ( P = 0.070). Conclusions: In this randomized controlled trial, pancrelipase failed to improve the change in BMI at 8 weeks in PC patients receiving chemotherapy.